A Parallel case?: The Irish in abolitionist thought and the emergence of white labor in the United States. Issue 1 (2nd January 2023) - McClurkin, Daniel T.
ABSTRACT: This article traces the rhetorical transformation from the Irish as an exemplum to the Irish as a historically situated demographic in U.S. abolitionist writings from the early to mid-nineteenth century. Through close readings of polemical essays, speeches, and newspaper articles, I argue that abolitionist writers such as David Walker, Samuel Cornish, Gerrit Smith, and Frederick Douglass begin to transition away from conceiving of the exploitation of Irish workers as a fraught, though generative comparative case to chattel slavery once a new demographic of native Irish Catholic emigrants are interpellated into the emergent category of "white labor." The Irish are thus initially used by abolitionist writers to contrast chattel slavery with other forms of labor exploitation under capitalism until the political utility of those comparisons began to wane as the Irish-American laborer proved socially and conceptionally antagonistic to free and enslaved black laborers.